Abuse of Authority in The Provision of Public Services - Akbar, Yogi Gumilar Saeful; Dewanti, Salma; Wulansari, Anggi Agustini; Lukmansyah, Lucky (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This journal article analyses the abuse of power in digital surveillance, focusing on the case of the Ministry of Communications and Digital (Komdigi) providing protection to online gambling sites. This research uses the literature study method to understand the mechanism of abuse of power and its supporting factors. The main findings show that weaknesses in internal controls and high financial incentives are the main drivers of this action. In addition, the development of digital technology creates new loopholes that are difficult to monitor using traditional methods. Analyses based on the theories of Utilitarianism, Virtue and Deontology Ethics reveal that these actions violate basic ethical principles, such as integrity, justice and public responsibility. Strategic recommendations include strengthening technology-based supervision, developing ethical competence of public officials, and adaptive regulation for the digital sector. This journal article is expected to serve as a reference in improving digital surveillance governance to prevent similar cases in the future.